Plant different, eat different? Insights from participatory agricultural research - Azzarri, Carlo; Haile, Beliyou; Letta, Marco (2022)
We examine the association between on-farm production diversity on household dietary diversity in Malawi using microdata collected as part of an environmentally sustainable agricultural intensification program. The program primarily focuses on the integration of legumes into the cropping system through maize-legume intercropping and legume-legume intercropping. Relative to staple cereals such as maize, legumes are rich in micronutrients, contain better-quality protein, and lead to nitrogen fixation. Given the systematic difference we document between program beneficiaries and randomly sampled non-beneficiary (control) households, we employ causal instrumental variables mediation analysis to account for non-random selection and possible simultaneity between production and consumption decisions. We find a significant positive treatment effect on dietary diversity, led by an increase in production diversity. Analysis of potential pathways show that effects on dietary diversity stem mostly from consumption of diverse food items purchased from the market made possible through higher agricultural income. These findings highlight that, while increasing production for markets can enhance dietary diversity through higher income that would make affordable an expanded set of food items, the production of more nutritious crops such as pulses may not necessarily translate into greater own consumption. This may be due to the persistence of dietary habits, tastes, or other local factors that favor consumption of staples such as maize and encourage sales of more profitable and nutritious food items such as pulses. Pulses are a more affordable and environmentally sustainable source of protein than animal source food, and efforts should be made to enhance their nutritional awareness and contribution to sustainable food systems and healthier diets.